Development of Reliability and Validity of Social Cohesiveness Rating Scale (SCRS) - Sanjenbam Sher Singh; Rajkumar Josmee Singh, Loukham Devarani, L. Hemochandra, Ram Singh (Indian Journal of Extension Education, 2022)
Natural Rubber is an important plantation crop and is gaining importance in North Eastern states of India due to increasing demand of rubber nationally and globally. Method of summated rating was administered in the construction of Social Cohesiveness Rating Scale (SCRS). Comprehensive literatures review and experts’ judgements were considered while identifying the item statements of SCRS. The scale was further standardized by establishing uni-dimensionality through administration of Exploratory Factor Analysis (EFA) using Principal Component with Varimax rotation to extract factors. The final scale consisted of 11 items. Spearman rank-order correlation coefficients (rs) on inter-rater reliability of the item statements range from 0.577 to 0.812. High concurrent validity as specified by rs = 0.75 (p < 0.01) signifies a good consideration on the validity of the SCRS to be administered in a research setting.